2(6d+3)=18-3(16d-3d)

Simple and best practice solution for 2(6d+3)=18-3(16d-3d) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6d+3)=18-3(16d-3d) equation:


Simplifying
2(6d + 3) = 18 + -3(16d + -3d)

Reorder the terms:
2(3 + 6d) = 18 + -3(16d + -3d)
(3 * 2 + 6d * 2) = 18 + -3(16d + -3d)
(6 + 12d) = 18 + -3(16d + -3d)

Combine like terms: 16d + -3d = 13d
6 + 12d = 18 + -3(13d)

Remove parenthesis around (13d)
6 + 12d = 18 + -3 * 13d

Multiply -3 * 13
6 + 12d = 18 + -39d

Solving
6 + 12d = 18 + -39d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '39d' to each side of the equation.
6 + 12d + 39d = 18 + -39d + 39d

Combine like terms: 12d + 39d = 51d
6 + 51d = 18 + -39d + 39d

Combine like terms: -39d + 39d = 0
6 + 51d = 18 + 0
6 + 51d = 18

Add '-6' to each side of the equation.
6 + -6 + 51d = 18 + -6

Combine like terms: 6 + -6 = 0
0 + 51d = 18 + -6
51d = 18 + -6

Combine like terms: 18 + -6 = 12
51d = 12

Divide each side by '51'.
d = 0.2352941176

Simplifying
d = 0.2352941176

See similar equations:

| -104=-6x-3x+4 | | 10a+5[a-3]=15 | | 3-x+3=5x | | 6-8x=7x-10+11 | | 14-3a+7a=94 | | 4q+4=-2q-8 | | -6(x-1)=14-2x | | 9x-27=9(11-x) | | 6-2x=-12 | | -2x+4(3x+5)=-60 | | 0.3x-0.4=2 | | 7p-5=69+8 | | 5(x+2)=(x+6) | | -8k+k=-14 | | x/4-x/3= | | .5x+5=17 | | 2(x+1)+4=16 | | 5-3(x-7)=26-2x | | 15+2x-3=2x+5 | | 5(4x+9)=9(2x+3) | | 0.5(14x+8)=6x+8 | | -4m-11=-3m-14 | | 6x+9x-21=105-6x | | -2k-5=-k+3 | | m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 | | P=22p | | 225-6x=30x+21 | | -3m+16=32-7m | | 2+5x=42 |

Equations solver categories